Mixing of binary fluids with composition-dependent viscosity in a T-shaped micro-device. (17th February 2015) - Galletti, Chiara; Arcolini, Giacomo; Brunazzi, Elisabetta; Mauri, Roberto
Abstract: The process of laminar mixing in a T-shaped micro-device is studied by direct numerical simulation for a model binary mixture, composed of two fluids having the same density and the same viscosity, yet presenting a strong fluidity of mixing effect, i.e. the viscosity of the mixture is a function of its composition. In all cases, the inlet streams remain separated up to a critical Reynolds number, corresponding to the transition from a vortex flow regime, with a double mirror symmetry, to an engulfment flow regime, with a point central symmetry. In the case of a positive fluidity of mixing, the onset of the engulfment regime is accompanied by a sharp increase of the degree of mixing, with the critical Re decreasing as the fluidity of mixing increases. On the contrary, when the fluid mixture has a larger viscosity than that of its pure components, a viscous layer forms at the confluence of the inlet flows, which tends to keep the two streams separated. Therefore, in this case, no sudden increase of the degree of mixing is observed at the onset of the engulfment regime. Abstract : Highlights: Laminar mixing in T-shaped micro-devices is studied by direct numerical simulation. The model mixture presents fluidity of mixing, Δ f, both positive and negative. For negative Δ f, no sudden increase of mixing efficiency at the engulfment. For positive or negligible Δ f, strong mixing increase at the engulfment.